2019
DOI: 10.1177/0149206318818723
|View full text |Cite
|
Sign up to set email alerts
|

To Merge, Sell, or Liquidate? Socioemotional Wealth, Family Control, and the Choice of Business Exit

Abstract: Access to the published version may require subscription. N.B. When citing this work, cite the original published paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
186
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(198 citation statements)
references
References 173 publications
(341 reference statements)
10
186
1
1
Order By: Relevance
“…Introducing the notion of socioemotional favoritism, they found that family CEOs are less likely to divest than non-family CEOs, especially in those foreign subsidiaries in which the family has a threshold ownership and those located in host countries where families have already lost ownership through past divestures. Chirico, Gomez-Mejia, Hellerstedt, Withers, and Nordqvist (2019) shed further light on FF post-entry processes, analyzing FF business exits. Drawing on behavioral agency theory, they found that FFs tend to endure increased financial distress to avoid losses to the family’s SEW embodied in the firm, and when exit is unavoidable, they are more likely to do so via mergers, which still saves some SEW, albeit less financially satisfying.…”
Section: The Evolution Of Ff Internationalization Research: a 30-yearmentioning
confidence: 99%
“…Introducing the notion of socioemotional favoritism, they found that family CEOs are less likely to divest than non-family CEOs, especially in those foreign subsidiaries in which the family has a threshold ownership and those located in host countries where families have already lost ownership through past divestures. Chirico, Gomez-Mejia, Hellerstedt, Withers, and Nordqvist (2019) shed further light on FF post-entry processes, analyzing FF business exits. Drawing on behavioral agency theory, they found that FFs tend to endure increased financial distress to avoid losses to the family’s SEW embodied in the firm, and when exit is unavoidable, they are more likely to do so via mergers, which still saves some SEW, albeit less financially satisfying.…”
Section: The Evolution Of Ff Internationalization Research: a 30-yearmentioning
confidence: 99%
“…In a related way, future studies could relate the existing findings to research on family firms. For example, family firms are less likely to exit than non-family firms (Chirico et al, 2019;Madanoglu et al, 2019); one may be interested in what the impact on family firms is when there is a separation event in the family business team.…”
Section: Discussionmentioning
confidence: 99%
“…Recent family business literature offers important insights in this respect. Chirico, Gómez-Mejia, Hellerstedt, Withers, and Nordqvist (2019), for example, draw on the socioemotional wealth perspective from family business research to find that family decision makers paradoxically respond more rigidly to internal and external distress cues and are thus reluctant to exit. However, their results suggest that, when confronted with different exit options, and when distress heuristics suggest that exit is unavoidable, family decision makers tend to rely on partial forms of exit (mergers) to preserve at least part of the family's socioemotional endowment.…”
Section: Family Management / Governance and Organization Studiesmentioning
confidence: 99%
“…In contrast, others suggest that the most relevant defining feature is the family, not the business entity. Therefore, exit from or sale of the business do not necessarily mean the cessation of family influence on business entities, Special Issue of Organization Studies on "Advancing Organization Studies in Family Business Research" because the controlling family may reinvest in different economic assets or new ventures (Chirico, Gómez-Mejia, Hellerstedt, Withers, and Nordqvist, 2019;Salvato, Chirico, and Sharma, 2010).…”
Section: Transgenerational Intention and Organization Studiesmentioning
confidence: 99%